Ferropenia sin anemia, más que un hallazgo de laboratorio - Martín Arsanios, Daniel (Pontificia Universidad Javeriana, 2018)
The deficit of iron without anemia is present in frequent pathologies of clinical practice, however, little is known about the importance, complications and benefits of the treatment. In this article, we describe an uptodate of the physiopathological pathways, the approach and treatment of the main pathologies related to iron deficiency without anemia. Methods; A complete and updated search of the scientific literature was made, in Medline, OVID, Lilacs, SciELO, EMBASE using a strategy defined with MeSH terms and not MeSH, limited to Spanish and English.